Evaluation Of Laboratory Errors And Other Causes In Spurious Thrombocytopenia - Chaithra V, Vanisri H , K T Athulya Krishna Kumar, Ravi Teja C N (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Pseudothrombocytopenia (PTCP) is an in vitro phenomenon characterized byspuriously low platelet counts without associated clinical bleeding. It often results from preanalyticalerrors, particularly ethylenediaminetetraacetic acid